SIRT7 antagonizes TGF-β signaling and inhibits breast cancer metastasis - Xiaolong Tang; Lei Shi; Ni Xie; Zuojun Liu; Minxian Qian; Fanbiao Meng; Qingyang Xu; Mingyan Zhou; Xinyue Cao; Wei-Guo Zhu; Baohua Liu (Nature Communications, 2017)
Metastatic disease is the major reason for breast cancer-related deaths; therefore, a better understanding of this process and its players is needed. Here the authors report the role of SIRT7 in inhibiting SMAD4-mediated breast cancer metastasis providing a possible therapeutic avenue.